Students' perception of teacher effectiveness and its relation to teacher's personality: The implications of these to the management of Divine Word College of Bangued - Buenafe, Imelda Carmen A. (Animo Repository, 1979)
The study aimed primarily to find out the students' perception of the effectiveness of the College Faculty of Divine Word College of Bangued. It sought also to discover some personality characteristics of the teachers and likewise established the relationship between these traits and the teachers' classroom behavior. The implications of the findings were also drawn to bear on the management of the school. The hypothesis tested was: Students' perception of the effectiveness of a teacher is not significantly related with the teacher's personality profile. In order to discover the personality characteristics of the teachers, the 16 Personality Factor Questionnaire was used. On the other hand, to determine their effectiveness, the Teacher Behavior Inventory (TBI) was utilized. Then, for statistical analysis, the following procedures were used: 1) frequency ranks, percentages, means and standard deviations and, 2) the Pearson-Product Moment Correlation for testing relationships and associations.